Diabetes and vaginal surgery are associated with mixed urinary incontinence in patients treated in a tertiary unit of Rio de Janeiro public healthcare system - Faria, Carlos Augusto; Dias, Juliana Branco; Garcia Rosa, Maria Luiza; Fonseca, Sandra Costa (Clinical and Biomedical Research, 2017)
Introduction: Urinary incontinence (UI) is prevalent in women, and the frequency of its clinical subtypes varies according to the population studied and the choice of diagnostic criteria. The aim of this study was to evaluate the distribution of the most common subtypes – stress urinary incontinence (SUI) and mixed urinary incontinence (MUI) – and their correlation with demographic, clinical and reproductive factors of patients seen at the university hospital of Universidade Federal do Rio de Janeiro. Methods: This cross-sectional study was conducted in a referral service of a tertiary care center. A retrospective analysis of records of 770 women referred to the urogynecologic outpatient clinic was performed. The clinical diagnosis of UI subtype was established in accordance with international standardization. Women presenting with SUI and MUI were compared in terms of age, reproductive history, comorbidities, medications used and gynecological surgeries. The effect of independent variables was assessed through multiple regression analyses. Results: The frequency of the clinical diagnosis of MUI and SUI was, respectively, 54.6% and 31.8%. Factors associated with MUI when compared with SUI were diabetes mellitus (odds ratio, OR = 1.75; 95% confidence interval, 95% CI = 1.08; 2.85) and perineoplasty (OR = 1.79; 95% CI = 1.18; 2.72). Age showed a borderline significance (p = 0.05). Conclusion: The distribution of UI subtypes was different from the distribution found in populational studies, which shows the specific aspects of women referred for specialized care. MUI was the most common subtype and was associated with previous vaginal surgery and diabetes mellitus when compared with SUI. Keywords: Urinary incontinence; Urge; urinary incontinence; stress; women’s health; epidemiology